case with abnormal tone decay and recruitment as measured by ABLB (auto) test
A case of abnormal tone decay demonstrating recruitment is reported. If we accept that recruitment is an artifact, the findings of this case are typical of ABLB auto presentation) test. On the other hand, if vie consider that recruitment is a fact the findings of this case are atypical of ABLB test indicating co-existence of the two lesions viz. cochlear and retrocochlear. If we accept that recruitment is an artifact, ABLB auto) test is not a useful test in differential diagnosis of cochlear Vs. retrocochlear as recruitment measured by ABLB auto) test is expected in all SN loss cases irrespective of tone decay provided factors like crossover, diplacusis, pulse rate and error of judgement are controlled. , number=1, journal=Journal of All India Institute of Speech and Hearing, author=MN, Vyasamurthy, year=1, month=1, pages=89-96